2005
DOI: 10.1111/j.0030-1299.2005.13665.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of consumer diversity and indirect facilitation on trophic level biomass and stability

Abstract: 2005. The influence of consumer diversity and indirect facilitation on trophic level biomass and stability. Á/ Oikos 110: 556 Á/566.The relationship between species diversity and the stability and production of trophic levels continues to receive intense scientific interest. Though facilitation is commonly cited as an essential underlying mechanism, few studies have provided evidence of the impact that indirect facilitation may have on diversity Á/ecosystem functioning relationships. In this laboratory study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…This conclusion is further supported by the low magnitude of species DE within the predator community (Figure 4). Our results are consistent with observations made, for example, in some marine ecosystems, where the increase of consumer biomass with higher consumer richness was largely explained by the 'complementarity effect' rather than by 'selection effects' (Duffy et al, 2003;Steiner et al, 2005). Increasing prey diversity allows for a greater niche complementarity for the predators with regard to their feeding modes (Snyder et al, 2006), and hence, may reduce interspecific interference among predators (Byrnes and Stachowicz, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion is further supported by the low magnitude of species DE within the predator community (Figure 4). Our results are consistent with observations made, for example, in some marine ecosystems, where the increase of consumer biomass with higher consumer richness was largely explained by the 'complementarity effect' rather than by 'selection effects' (Duffy et al, 2003;Steiner et al, 2005). Increasing prey diversity allows for a greater niche complementarity for the predators with regard to their feeding modes (Snyder et al, 2006), and hence, may reduce interspecific interference among predators (Byrnes and Stachowicz, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, McMahon et al (2012) showed that declines in species richness induced by exposure to chlorothalonil reduced decomposition and water clarity and elevated primary production and dissolved oxygen in a mesocosm experiment. Further, zooplankton diversity can be critical to the algal community with high zooplankton diversity resulting in an increase in large, grazer resistant algae ( > 35 µm chlorophyll a; Steiner et al 2005). In this study, carbamazepine increased Elimia and decreased Helisoma standing biomass, increased invertebrate diversity and decreased Daphnia pulex abundance, which in turn affected ecosystem characteristics such as dissolved nutrient concentrations, primary production and decomposition.…”
Section: Discussionmentioning
confidence: 69%
“…Changes in diversity and species composition can profoundly alter ecosystem dynamics (Chaplin et al 1997, Steiner et al 2005, Wojdak 2005). utilized a mesocosm experiment to demonstrate the importance of both species richness and composition to productivity, respiration and decomposition in freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through complex trophic interactions, a highly diverse assemblage of grazers (with multiple feeding behaviors in a functional group) may have a null effect on the biomass of the lower trophic level, as direct consumption is balanced by indirect effects of predation. Due to the increased functional redundancy and weakened trophic effect, increasing the diversity of predator feeding behavior will consequently stabilize the system because the niche of an extinct species will soon be able to be occupied by others (Steiner et al 2005). Such a stabilization effect of predators with diverse feeding behaviors has also been studied in various systems, especially when predators engage in omnivory (Bruno & O'Connor 2005), cannibalism, or intraguild predation (Finke & Denno 2004).…”
Section: Discussionmentioning
confidence: 99%